ANALISIS TANGGUNG JAWAB PELAKU USAHA PT. JASA MARGA TERHADAP PELANGGARAN HAK KESELAMATAN KONSUMEN PENGGUNA JALAN TOL DITINJAU DARI PERATURAN PEMERINTAH NOMOR 15 TAHUN 2005 TENTANG JALAN TOL. - Mayskhye Techtonia; A.M Tri Anggraini (Jurnal Hukum Adigama, 2018)
Roads are one of the most important transportation infrastructures in people's lives and have an important role in the efforts to develop the life of the nation and state, especially the construction of toll roads that are safe and comfortable for journeys. But along with the development of the era, resulting in many problems that occur related to toll road safety, so the question arises: How is legal protection for consumers of toll road users in the right to safety on the highway? And How the Responsibilities of Business Actors PT. Jasa Marga regarding violations of consumer safety of toll road users in terms of Government Regulation Number 15 of 2005 concerning toll roads? As normative legal protection road users a toll had been arranged in several regulations which includes government regulation number 15 of 2005 and completed explicitly by law number 8 of 1999 on consumer protection. But what envisaged in the regulation in protecting and responsibility of have been given by PT. Jasa Marga not fully been implemented especially consumers road users toll in the soles safety on the highway